2019
DOI: 10.1002/uog.20383
|View full text |Cite
|
Sign up to set email alerts
|

Rare autosomal trisomies: comparison of detection through cell‐free DNA analysis and direct chromosome preparation of chorionic villus samples

Abstract: Objective Direct chromosome preparations of chorionic villus samples (CVS) and cell‐free DNA (cfDNA) testing both involve analysis of the trophoblastic cell lineage. The aim of this study was to compare the spectrum of rare autosomal trisomies (RATs) detected by these two approaches and assess the available information on their clinical significance. Methods Data from 10 reports on genome‐wide cfDNA testing were pooled to determine which chromosomes were most frequently involved in RAT‐positive cases, and preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
109
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(116 citation statements)
references
References 54 publications
5
109
1
Order By: Relevance
“…In all 28 cases, the clinical follow-up was normal. Benn et al reviewed the types of RAT identified following CVS, as reported in 10 recently published cfDNA studies, and found that the clinical outcome of cases with cfDNA analysis positive for RATs mostly involved the birth of an apparently normal baby (40%) or a miscarriage/fetal loss (27%), for which screening tests are not recommended 6 . There was a weak association between RATs and pregnancy complications, such as fetal growth restriction and fetal abnormalities, in the tested population.…”
mentioning
confidence: 99%
“…In all 28 cases, the clinical follow-up was normal. Benn et al reviewed the types of RAT identified following CVS, as reported in 10 recently published cfDNA studies, and found that the clinical outcome of cases with cfDNA analysis positive for RATs mostly involved the birth of an apparently normal baby (40%) or a miscarriage/fetal loss (27%), for which screening tests are not recommended 6 . There was a weak association between RATs and pregnancy complications, such as fetal growth restriction and fetal abnormalities, in the tested population.…”
mentioning
confidence: 99%
“…Previous reports have shown that suspected RAAs at NIPT can be associated with an increased risk of CPM. 7,10,13,14 In this study, fetal demise occurred in a case with undiagnosed trisomy 22. Moreover, another woman with false positive results for fetal monosomy 16 ended the pregnancy owing to fetal structural anomalies.…”
Section: Discussionmentioning
confidence: 61%
“…However, other chromosomal abnormalities are usually detected concurrently due to the high throughput of NIPT. Benn et al demonstrated that the relative frequency of trisomy 2 was 3.4% in a total of 499 RATs identified by cfDNA analysis [27]. Wan et al identified 2 cases of trisomy 2 in 59 cases with high risk of RAT detected by NIPT and one of the positive case turned out to be a homozygosity of chromosome 2 by vertification of CMA [11].…”
Section: Discussionmentioning
confidence: 99%